Membentuk Karakter Siswa SMA Melalui Karakter Religius pada Novel Mahamimpi Anak Negeri Karya Suyatna Pamungkas: Shaping the Character of High School Students Through Religious Characters in the Novel Maha Dreaming Children of the Country by Suyatna Pamungkas - Abdulfatah, Muhammad Rois; Widodo, Sahid Teguh; Rohmadi, Muhammad (Pedagogia : Jurnal Pendidikan, 2018)
This research is to know the values of religious character in the novel Mahamimpi Anak Negeri by Suyatna Pamungkas to build the character of high school students. The goal of this research is the formation of the religious character of high school students through the novel in the novel Mahamimpi Anak Negeri by Suyatna Pamungkas. This research method is descriptive qualitative. The technique of writing this data using content analysis. The results of this study First, the results of the discourse analysis found that describes the education of religious characters in the novel Mahamimmpi Anak Negeri Suyatna Pamungkas. Both discussions about the religious character of high school students through interviews with teachers.